Catalytic oxygenation of sp3 "C–H" bonds with Ir(iii) complexes of chelating triazoles and mesoionic carbenes. Issue 2 (11th November 2014) - Hohloch, Stephan; Kaiser, Selina; Duecker, Fenja Leena; Bolje, Aljoša; Maity, Ramananda; Košmrlj, Janez; Sarkar, Biprajit
Abstract : Ir(iii ) complexes with chelating triazole and mesoionic carbene ligands are potent pre-catalysts for the direct oxygenation of C–H bonds. Abstract : Cp*-Ir(iii ) complexes with additional chelating ligands are known active pre-catalysts for the oxygenation of C–H bonds. We present here eight examples of such complexes where the denticity of the chelating ligands has been varied from the well-known 2, 2′-bpy through pyridyl-triazole, bi-triazole to ligands containing pyridyl-triazolylidene, triazolyl-triazolylidene and bi-triazolylidenes. Additionally, we also compare the catalytic results to complexes containing chelating cyclometallated ligands with additional triazole or triazolylidene donors. Single crystal X-ray structural data are presented for all the new complexes that contain one or more triazolylidene donors of the mesoionic carbene type. We present the first example of a metal complex containing a chelating triazole-triazolylidene ligand. The results of the catalytic screening show that complexes containing unsymmetrical donors of the pyridyl-triazole or pyridyl-triazolylidene types are the most potent pre-catalysts for the C–H oxygenation of cyclooctane in the presence of either m -CPBA or NaIO4 as a sacrificial oxidant. These pre-catalysts can also be used to oxygenate C–H bonds in other substrates such as fluorene and ethyl benzene. The most potent pre-catalysts presented here work with a lower catalyst loading and under milder conditions while delivering better product yields in comparison with related literature known Ir(iii ) pre-catalysts. These results thus point to the potential of ligands with unsymmetrical donors obtained through the click reaction in oxidation catalysis.